Budget Based Estimation of Aggregate Plan Resources and Fiscal Performance Indicators a Comparison among 25 States - Planning Commission (Planning Commission, 2001)
Higher percentage reflects higher revenue capability from State's own taxes to sustain incremental debt. Excludes share in central taxes Higher percentage reflects higher revenue capability injected through GOI revenue transfers to sustain incremental debt. GOI revenue devolution comprises share in Central taxes and plan and non-plan grants. Higher percentage reflects higher funding of State's net borrowings by GOI. State's borrowing from GOI include debt component of Central Assistance and CSS/CPS only. Higher percentage reflects higher proportion of net borrowings funding Plan expenditure. Plan expenditure includes expenditure on CSS/CPS. Higher percentage reflects higher proportion of net borrowings funding capital outlay.
Planning Commission, (Financial Resources Division), Government of India
Planning Commission (Financial Resources Devision Government of India